The Effect of Applying the Audio-Lingual Method Using the First Volume of the Book “Arabiah Baina Yadaik” in Improving Speaking Skills in Students of the Imam Syafi'i Enrekang Islamic Boarding School - Athaya Bunyamin, Zhafran; Ilyas, Hamka; Munir, Munir; Abunawas, Kamaluddin; Rappe, Rappe (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
This study discusses the effect of applying the audio-lingual method using the first volume of the book “Arabiah Baina Yadaik” in improving speaking skills of students at the Imam Syafi'i Enrekang Islamic Boarding School. The type of research for this research is quantitative experimental research, and for the data collection method is observation, testing, and documentation. As for the results of the study, the researcher believes that the application of the audiolingual method by using the book Arabia baina yadaik volume one is effective in improving speaking skills in students of the Imam Syafi'i Enrekang Islamic boarding school. The implication of this research is to increase knowledge, attention, and insight for oneself in learning Arabic.